2015
DOI: 10.1016/bs.apar.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Cryptosporidium and Giardia, with an Emphasis on Bovines and Recent Epidemiological Findings

Abstract: Cryptosporidium and Giardia are two common aetiological agents of infectious enteritis in humans and animals worldwide. These parasitic protists are usually transmitted by the faecal-oral route, following the ingestion of infective stages (oocysts or cysts). An essential component of the control of these parasitic infections, from a public health perspective, is an understanding of the sources and routes of transmission in different geographical regions. Bovines are considered potential sources of infection fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 315 publications
(464 reference statements)
2
57
0
Order By: Relevance
“…11,20,21 The high prevalence of Cryptosporidium infection documented in our study may be due to poor sanitation, poverty, and lack of diagnostic tools. 3,22 Since our study was performed in late summer and early autumn, these results might also reflect the seasonality of Cryptosporidium transmission. [23][24][25] We noted that the prevalence of Cryptosporidium was different among the towns and therefore carried out a stratified analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,20,21 The high prevalence of Cryptosporidium infection documented in our study may be due to poor sanitation, poverty, and lack of diagnostic tools. 3,22 Since our study was performed in late summer and early autumn, these results might also reflect the seasonality of Cryptosporidium transmission. [23][24][25] We noted that the prevalence of Cryptosporidium was different among the towns and therefore carried out a stratified analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also found that raising cattle, especially calve, was a risk factor for human Cryptosporidium infection. 3,31 In this area, cattle usually graze on the nearby hills away from human settlements, thus human-cattle contacting is less frequent. Horses, cats, and dogs are primarily infected with host-specific Cryptosporidium species or genotypes, and therefore, the actual risk of zoonotic transmission of these animals may be low.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidiosis is an important insidious disease of wide variety of animals, including humans, caused by apicomplexan protozoa of the genus Cryptosporidium (Abeywardena et al, 2015). Till date, 26 Cryptosporidium species and more than 70 genotypes have been recognized (Qi et al, 2015) and among them the most important species infecting bovines are C. parvum, C. andersoni and C. bovis (bovine genotype B) (Mirhashemi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most Giardia infections naturally occurring in wildlife are caused by zoonotic species, which are considered to have been introduced into wildlife habitats and, once established, maintained by direct contact or environmental routes (THOMPSON, 2013;ABEYWARDENA et al, 2015). The study region (Galicia, northwest Spain) is characterized by an important livestock sector and extensive rural areas, where farmers usually applied slurry as manure in the grasslands.…”
Section: Resultsmentioning
confidence: 99%